Dasar Pertimbangan Hakim Menetapkan Hak Asuh Anak Kepada Suami Selaku Pemohon pada Pengadilan Agama Jambi - Maryati Maryati (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Husband or wife are parents who have the same right and obligation to take care of their children, but because of a divorce, the control and management of the children cannot be done together, resulting in a dispute between the two parents. On the basis of this, the child will bear the consequences of the divorce carried out by both parents. The purposes of this study are: a) To find out and analyze what is the basis for the judge's consideration in determining child custody given to the husband as the applicant at the Jambi Religious Court and b) To find out and analyze the legal consequences of child custody given to the husband as the applicant. The research method used in this paper is an empirical juridical approach. The conclusion of this study is that in case Number 122/Pdt.G/2019/PA. The consideration of the Panel of Judges in determining the custody of a child who has not yet reached the age of 12 years to his biological father psychologically is for the sake of realizing the problems and interests of the child himself, because if the child is assigned to his biological mother, which is based on the facts at trial the biological mother does not have the skills and the ability to meet the interests of the child normally.